Biogeochemistry of high altitude soils on ophiolites in the Western Italian Alps - Michele D'Amico; Franco Previtali (2011)
High Mg, Fe, heavy metals, pH values close to neutrality and high base status characterize “serpentine soils”; the low Ca/Mg ratios and the high metal contents can cause stress on biological communities: the vegetation often shows a low cover and a peculiar species composition. Chemical and biological properties of alpine and arctic “serpentine soils” have seldom been studied worldwide. 97 soil pits (associated with phytosociological surveys) were analyzed above the treeline in Mont Avic Natural Park (Val d’Aosta, north-western Italy). The aim was to recognize pedogenic processes, mobility and bioavailability of metals and nutrients, to statistically identify edaphic properties influencing vegetation and possible stress symptoms on microbial and arthropodal communities. On serpentinite, meta-gabbros and calcschists, in cold and wet high-altitude climates (annual temperatures below 2°C and rainfall below 1300mm/y), soils are acidic, with pH values increasing with altitude and cryogenic or erosive disturbances. Cryoturbation, erosion and deposition “rejuvenate” soils by adding unweathered material into surface horizons: the soil chemistry depends on substrate, and metal concentration is increased in biologically-active horizons on serpentinite. Despite the weak soil development, metal speciation shows a strong mobilization and bioavailability, caused by waterlogging at snowmelt and acidity. On serpentinite, high bioavailable Ni is related with the absence of some common acidophilous species, despite the low pH values, and with the presence of serpentine-endemic species. Ca/Mg ratios, nutrients and pH values are not statistically significant. Bioavailable metals don’t significantly influence micro-arthropod communities. Microbial activity and stress indices are not related either with substrate or metal content.